New insights into the chemistry of Coenzyme Q-0: A voltammetric and spectroscopic study - Gulaboski, Rubin; Bogeski, Ivan; Kokoskarova, Pavlinka; Haeri, Haleh H; Mitrev, Sasa; Stefova, Marina; Stanoeva, Jasmina Petreska; Markovski, Velo; Mirčeski, Valentin; Hoth, Markus; Kappl, Reinhard (Elsevier BV, 2016)
Coenzyme Q-0 (CoQ-0) is the only Coenzyme Q lacking an isoprenoid group on the quinoid ring, a feature important for its physico-chemical properties. Here, the redox behavior of CoQ-0 in buffered and non-buffered aqueous media was examined. In buffered aqueous media CoQ-0 redox chemistry can be described by a 2-electron-2-proton redox scheme, characteristic for all benzoquinones. In non-buffered media the number of electrons involved in the electrode reaction of CoQ-0 is still 2; however, the number of protons involved varies between 0 and 2. This results in two additional voltammetric signals, attributed to 2-electrons-1H(+) and 2-electrons-0H(+) redox processes, in which mono- and di-anionic compounds of CoQ-0 are formed. In addition, CoQ-0 exhibits a complex chemistry in strong alkaline environment. The reaction of CoQ-0 and OH(-) anions generates several hydroxyl derivatives as products. Their structures were identified with HPLC/MS. The prevailing radical reaction mechanism was analyzed by electron paramagnetic resonance spectroscopy. The hydroxyl derivatives of CoQ-0 have a strong antioxidative potential and form stable complexes with Ca(2+) ions. In summary, our results allow mechanistic insights into the redox properties of CoQ-0 and its hydroxylated derivatives and provide hints on possible applications.
Keywords: Coenzyme Q-0 Voltammetry EPR Hydroxyl benzoquinones Antioxidants Calcium binding